Actualizing hope and joy in K-12 curricula through Daisaku Ikeda’s human education - Nai-Cheng Kuo; Amy Wood; Kyra Williams (Goodwood Publishing, 2021)
Purpose: Our study aims to create a framework grounded in Daisaku Ikeda’s philosophy of education for educators and researchers to implement and evaluate human education in the classroom. Research Methodology: We first synthesized the eighteen chapters by scholars involved in Ikeda studies, published in the book entitled: Hope and Joy in Education: Engaging Daisaku Ikeda across Curriculum and Context to discover the main themes in Ikeda’s human education. Based on these themes, we selected six children’s stories developed by Ikeda to design lessons. We then conducted surveys with ten K-12 teachers across disciplines and school districts to explore their perspectives toward humanity and their feedback on our lesson design. Results: Our finding indicates that creating hope and joy in education is inseparable from human revolution, value creation, happiness, the greater self, global citizens, as well as life and death. In addition, the participant’s responses to the survey questions help educators and researchers understand what K-12 teachers look for in order to implement lessons on humanity more efficiently and effectively. Limitations: By no means would we consider our lesson design exemplary or applicable in all different contexts. Instead, we consider these lessons a starting point to continue exploring a better way to teach humanity in school. Contribution: Seeing examples of lesson plans on humanity and learning from K-12 teachers’ perspectives provide an aspect for educators and researchers to use, extend, or expand the present study to bring hope and joy to students in their local contexts.